2020
DOI: 10.1002/slct.202003135
|View full text |Cite
|
Sign up to set email alerts
|

Study of Spin Crossover Property of a Series of X‐OMe‐SalEen (X=6, 5 and 4) Based Fe(III) Complexes

Abstract: Three complexes bearing the molecular formula [Fe(X‐OMe‐SalEen)2]NCY⋅nH2O; X=6, Y=S, n=0 (1); X=5, Y=S, n=1.5 H2O (2) and X=4, Y=Se, n=0 (3), where 6‐OMe‐SalEen=2‐((E)‐(2‐(ethylamino)ethylimino)methyl)‐6‐methoxyphenol, 5‐OMe‐SalEen=2‐((E)‐(2‐(ethylamino)ethylimino)methyl)‐5‐methoxyphenol, and 4‐OMe‐SalEen=2‐((E)‐(2‐(ethylamino)ethylimino)methyl)‐4‐methoxyphenol, have been synthesized, characterized and their spin crossover behavior has been studied. The ligands differ in the position of the methoxy group (orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Two or more peaks can be observed for all the three complexes, one ranging from 300 to 450 nm and the others ranging from 450 to 800 nm. The peak below 400 nm is due to the π–π* transition of the ligand. , Complex 2 , which has no substituent, exhibits a λ max of 331 nm for the π–π* transition. In 1 , the mesomeric effect of the methoxy group (OMe) reduces the π–π* energy gap, leading to a bathochromic effect (λ max = 354 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two or more peaks can be observed for all the three complexes, one ranging from 300 to 450 nm and the others ranging from 450 to 800 nm. The peak below 400 nm is due to the π–π* transition of the ligand. , Complex 2 , which has no substituent, exhibits a λ max of 331 nm for the π–π* transition. In 1 , the mesomeric effect of the methoxy group (OMe) reduces the π–π* energy gap, leading to a bathochromic effect (λ max = 354 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Thermogravimetric measurements were carried out for 1 – 3 , and the data are provided in Figure S14. It was found that 3 is thermally very stable, with a decomposition temperature of 448 K. ,,,, This type of thermally stable SCO molecule with a high transition temperature (366 K) can be used to prepare magnetic switches and devices for high-temperature applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCO behavior is greatly influenced by various factors such as counter anion, ligand field strength, and solvent mole-cules present in the crystal lattice. [36][37][38][39][40] Our group reported a series of complexes [Fe(5-X-SalEen) 2 ]NCS (X = Me, Br, OMe and 5-X-SalEen = condensation product of 5-substituted salicylaldehyde and N-ethylethylenediamine) and showed that with increasing ligand field strength the spin transition became more abrupt and T 1/2 shifted towards the higher temperature. 36 Pfrunder et al studied the SCO properties of [Co(terpy) 2 ] 2+ (terpy = terpyridine) complex cation under different anionic environment made up of 1,3-diiodotetrafluorobenzene (1,3-DITFB) or 1,3,5-triiodotrifluorobenzene (1,3,5-TITFB) anions.…”
Section: Introductionmentioning
confidence: 99%
“…The SCO behavior is greatly influenced by various factors such as counter anion, ligand field strength, and solvent molecules present in the crystal lattice. 36–40 Our group reported a series of complexes [Fe(5-X-SalEen) 2 ]NCS (X = Me, Br, OMe and 5-X-SalEen = condensation product of 5-substituted salicylaldehyde and N -ethylethylenediamine) and showed that with increasing ligand field strength the spin transition became more abrupt and T 1/2 shifted towards the higher temperature. 36…”
Section: Introductionmentioning
confidence: 99%